Desempenho auditivo ao longo do tempo em usuários de implante coclear com perda auditiva pós-lingual - Brazorotto, Joseli Soares (2013)
Purpose: Evaluating the hearing accomplishment over time and to investigate the prognostic factors related. Methods: A retrospective cohort study carried out through analysis the medical records of 57 patients with post-lingual hearing loss and cochlear implant for at least 12 months. To sustain our method we applied the Kaplan-Meier method and the logrank test for analysis of speech perception over time and the possible influence of factors such as gender, education, duration of hearing loss, age at implantation, etiology and device’s brand, on the outcome studied. Results: In only 12 months after implant activation, more than half of the cohort already had satisfactory scores on the test of speech perception. The logrank test had not indicated difference among the covariates tested. There was a significant difference between the hearing results pre and post cochlear implant. Conclusion: The hearing performance after 12 months using the IC exceeds the criterion for the majority of individuals with post-lingual hearing loss, regardless of prognostic factors evaluated, but not all respondents.